Ecological and economic influencing factors on the spatial and temporal evolution of carbon balance zoning in the Taihu Basin - Wang, Yazhu; Wang, Yuxiang; Duan, Xuejun (Frontiers in Ecology and Evolution, 2024)
The escalation in carbon dioxide concentration has precipitated global climate warming, accentuating ecological and environmental concerns. Notably, China stands as the world's largest carbon emitter, with the Taihu Lake basin emerging as a carbon-intensive region within the country. This paper undertakes a comprehensive analysis spanning 2005 to 2020, calculating the economic contribution coefficient of carbon emissions and the ecological carrying coefficient of carbon absorption in the Taihu Lake basin. The study includes a delineation of carbon balance zones and an exploration of the geographical and spatial influences of both ecosystem and economic factors. The overarching trend in carbon emissions within the Taihu Lake Basin initially exhibited rapid growth, followed by a fluctuating decline, with the pivotal year being 2012, recording the apex of emissions at 575.8293 million tons. Concurrently, total carbon absorption demonstrated a fluctuating growth trajectory, ascending from 82.3503 million tons in 2005 to 85.6488 million tons in 2020. The carbon emission intensity in the basin manifested a pattern of high concentration in the northeast and low concentration in the southwest, while the carbon absorption intensity displayed the inverse pattern. The carbon balance across the Taihu Lake Basin revealed a spatial incongruity, characterized by a suboptimal pattern in the northeast and a favorable pattern in the southwest. Zhejiang Province emerged as an ecological stronghold within the basin, acting as the primary carbon sink functional area. Urban built-up areas and forested regions emerged as principal influencers of carbon balance in the Taihu Lake basin. Urban construction land, population density, and arable land area were identified as primary contributors to carbon emissions, whereas per capita GDP, forests, grasslands, and water bodies were identified as main contributors to carbon absorption in the watershed.